Association of \(TEX15\) rs142485241 with male infertility in 429 Vietnamese individuals - Thuy Duong, Nguyen; Duc Duy, La; Van Hai, Nong (Academia Journal of Biology, 2022)
Male infertility is a reproductive disease caused by various factors, including environmental factors and genetic defects. Thousands of genes have been identified to cause and associate with male infertility, such as TEX15. Our study aimed to identify the association between the polymorphism TEX15 rs142485241 and male infertility. Total DNAs were extracted from the whole blood of 429 unrelated Vietnamese individuals, including 202 healthy controls and 227 patients with male infertility. The genotypes and alleles of the polymorphism were determined by the PCR-RFLP method. The data were analyzed by statistical methods to assess the association of TEX15 rs142485241 with male infertility. The results showed that the distribution of genotypes of the polymorphism followed the Hardy-Weinberg equilibrium (p-value > 0.05). However, no association was established between the polymorphism TEX15 rs142485241 and male infertility in the three models (additive, dominant, and recessive) (p-value > 0.05). This study would contribute to the knowledge about the association of TEX15 with male infertility in the Vietnamese population.